Genetic variation in the flowering and yield formation of timothy (Phleum pratense L.) accessions after different photoperiod and vernalization treatments - Jokela, Venla; Trevaskis, Ben; Seppänen, Mervi M. (Frontiers in Plant Science, 2015)
Timothy is a perennial forage grass grown commonly in Boreal regions. This study explored the effect of vernalization and photoperiod (PP) on flowering and growth characteristics and how this related to changes in expression of three flowering related genes in accessions from different geographic origin. Large variation was found in accessions in their vernalization and PP responses. In southern accessions vernalization response or requirement was not observed, the heading date remained unchanged, and plants flowered without vernalization. On the contrary, northern types had obligatory requirement for vernalization and long PP, but the tiller elongation did not require vernalization at 16- h PP. Longer vernalization or PP treatments reduced the genotypical differences in flowering. Moreover, the vernalization saturation progressed stepwise from main tiller to lateral tillers, and this process was more synchronized in southern accessions. The expression of PpVRN1 was associated with vernalization while PpVRN3 accumulated at long PP. A crucial role for PpVRN3 in the transition to flowering was supported as in southern accession the transcript accumulated in non-vernalized plants after transfer to 16-h PP, and the apices transformed to generative stage. Differences in vernalization requirements were associated with variation in expression levels of PpVRN1 and PpVRN3, with higher expression levels in southern type. Most divergent transcript accumulation of PpMADS10 was found under different vernalization conditions. These differences between accessions can be translated into agronomic traits, such as the tiller composition of canopy, which affects the forage yield. The southern types, with minimal vernalization response, have fast re-growth ability and rapidly decreasing nutritive value, whereas northern types grow slowly and have better quality. This information can be utilized in breeding for new cultivars for longer growing seasons at high latitudes.